Definition of nocturnal gastroesophageal reflux for studies on respiratory diseases. (3rd May 2016) - Emilsson, Össur Ingi; Benediktsdóttir, Bryndís; Ólafsson, Ísleifur; Cook, Elizabeth; Júlíusson, Sigurður; Berg, Sören; Nordang, Leif; Björnsson, Einar Stefán; Guðlaugsdóttir, Sunna; Guðmundsdóttir, Anna Soffía; Janson, Christer; Gislason, Thorarinn
ABSTRACT: Objective Nocturnal gastroesophageal reflux (nGER) has been associated with respiratory diseases. Our aim was to study a questionnaire method to identify nGER subjects with respiratory involvement in a general population.Material and methods A subgroup of Icelandic participants in the European Community Respiratory Health Survey III (ECRHS III) reporting symptoms of nGER ( n  =  48) as well as age and gender paired controls ( n  =  42) were studied further by a structured interview, questionnaires, laryngeal fibrescopy, and exhaled breath condensate. A subgroup underwent 24-h oesophageal pH impedance (24-h MII-pH) measurements. Symptoms of nGER were assessed with a modified version of the reflux disease questionnaire (RDQ), where symptoms were divided into daytime and nocturnal. A report of nGER both at baseline and at follow-up was defined as persistent nGER.Results Participants reporting persistent nGER had significantly more signs of laryngopharyngeal reflux according to the reflux finding score than those without nGER (Mean ± SD: 5.1 ± 2.3 vs. 3.9 ± 2.2, p  =  0.02). Of the 16 persistent nGER subjects that underwent 24-h MII-pH, 11 had abnormal gastroesophageal reflux, but none of three control subjects (69% vs. 0%). Pepsin was more commonly found in exhaled breath condensate in the nGER group (67% vs. 45%, p  =  0.04).Conclusions Participants with nGER symptoms at least once a month, reported on two occasions, had a high level of positive 24-h MII-pH measurements, laryngeal inflammation and pepsin in exhaled breath condensate. This nGER definition identified a representable group for studies on nGER and respiratory diseases in a general population.